2020
DOI: 10.14314/polimery.2020.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment of incrementally produced components in FFF (Fused Filament Fabrication) technology

Abstract: The aim of the conducted research was to examine the possibility of using chemical and physical methods of surface treatment of elements printed on a 3D printer. Elements were printed from polylactide (PLA) and acrylonitrile-butadiene-styrene (ABS) -materials most commonly used in fused filament fabrication (FFF) technology. Roughness measurements were made to assess the quality of individual methods. The best surface smoothness results were obtained during abrasive paper processing and after applying epoxy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Therefore, as the layer height increases, the surface quality gets worse. Mrówka et al 15 identified the same behavior when analyzing layer heights between 0.06 and 0.4 mm after printing acrylonitrile butadiene styrene (ABS) and PLA parts. Buj-Corral et al 16 reached the same conclusion in their studies of the printing of PLA when using layer heights between 0.05 and 0.25 mm.…”
Section: Introductionmentioning
confidence: 75%
“…Therefore, as the layer height increases, the surface quality gets worse. Mrówka et al 15 identified the same behavior when analyzing layer heights between 0.06 and 0.4 mm after printing acrylonitrile butadiene styrene (ABS) and PLA parts. Buj-Corral et al 16 reached the same conclusion in their studies of the printing of PLA when using layer heights between 0.05 and 0.25 mm.…”
Section: Introductionmentioning
confidence: 75%